Book Review: Imam Rabbani Abu'l-Barakāt Aḥmad ibn 'Abd al-Ahad ibn Zayn al-Abidin al Faruk al-Sirhindī. Mukashifate Aynia. Trans. Dr. Md. Abu Baker Siddique. Narayanganj: Hakimabad Khanka-e-Mozaddedia. 6. baskı, 2009. ISBN 984-70240-0021-7 - Chowdury, Saeyd Rashed Hasan (CenRaPS Journal of Social Sciences, 2024)
This scholarly examination critically assesses the literary work titled "Mukashifate Aynia", authored by Imam Rabbani, also known as Abu'l-Barakāt Aḥmad ibn 'Abd al-Ahad ibn Zayn al-Abidin al-Faruk al-Sirhindī. In "Mukashafat al-Ayniyya," Imam Rabbani underscores the importance of strict adherence to Sharia. He contends that individuals deviating from full compliance with the Quran and the Sunnah of Prophet Muhammad (Pbuh) will not reap benefits in either the temporal realm or the afterlife. Imam Rabbani elucidates a comprehensive framework for individuals aspiring to be steadfast adherents of Sharia, delineating its constituents into three fundamental elements: knowledge, action, and sincerity. According to Imam Rabbani, sincerity is the linchpin encompassing knowledge, action, and the quintessence of Sharia. He posits that achieving complete sincerity necessitates affiliation with a Sufi order. He extols the Naqshbandi-Mujaddidi Sufi order as the preeminent, uncomplicated, and profoundly meaningful choice among these orders. Imam Rabbani contends that the Sufi order is not merely a semantic designation but an integral facet of Sharia. He believes no viable alternative to the Sufi order exists when sincerity is wholeheartedly embraced. Within this framework, he underscores the imperative for all Muslims to align themselves with the Sufi order. Furthermore, Imam Rabbani accentuates the undeniable significance of the Naqshbandi-Mujaddidi Sufi order in fostering virtuous character. In "Mukashafat al-Ayniyya," he adeptly reconciles the tenets of Sharia with those of the Sufi order, presenting a cohesive synthesis of their principles. The work emphasises the adherence to Sharia and underscores the pivotal role of spiritual education in shaping individual character. Imam Rabbani emphasises the influential role of virtuous spiritual guides and mentors while critiquing insincere or hypocritical figures within the spiritual realm. Imam Rabbani intricately explores the mystical experiences of revered Sufis and delves into the intricate terminology unique to Sufism in the meticulous division of his work into twenty-nine sections. Concurrently, he expounds upon the concept of "The Journey (Seyr-u Suluk)," providing nuanced insights into the various levels and dimensions of Sufism.